Rain-responsive polypyrrole-graphene/PtCo electrodes for energy harvest. (20th September 2018) - Wang, Yingli; Duan, Jialong; Zhao, Yuanyuan; Jiao, Zhengbo; He, Benlin; Tang, Qunwei
Abstract: Renewable energy conversion has become one of the major strategies to solve energy crisis and environmental pollution. Tremendous energy is released during the raining process, however rain energy is always considered as a waste energy without further utilization. We present here experimental realization of physical proof-concept rain-response electrodes from polypyrrole (PPy), PPy-graphene and PPy-graphene/PtCo for rain energy harvest. By obeying charging/discharging mechanism of cation (rain)/electron (electrode) electrical double-layer (EDL) pseudocapacitances at rainwater/electrode interfaces, periodical current and voltage signals are produced under the stimulation of simulated rain droplets. The energy conversion device made from PPy-graphene/PtCo achieves a maximized peak current of 4.91 μA/droplet, a peak voltage of 320.62 μV/droplet, yielding a power of 1161.38 pW/droplet. The results demonstrate that the improved current and voltage outputs are highly dependent on increased electron concentration at electrode surface. This work may extend our knowledge to advanced energy conversion devices for waste energy harvest. Graphical abstract: A rain-responsive polypyrrole-graphene/PtCo electrode is made to harvest rain. Image 1 Highlights: Electron-enriched electrodes are utilized to harvest rain energy. The electrodes are made with polypyrrole (PPy), PPy-graphene or PPy-graphene/PtCo. The electrodes achieve maximized current of 4.91 μA and voltage of 320.62 μV. Electrical signals are improved by increasing electron concentration of electrodes.